Evaluation of The Kirkpatrick Model of Employment Training Center For Manpower Training and Transmigration (BPTT) Jambi Province - Syamsul Huda; M Gazali (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
This study discusses the preparation of work skills as the main requirement for creating a reliable workforce in filling jobs. This research was conducted with a descriptive evaluation approach using the four levels evaluation model or Kirkpatrick's model, which includes: reaction, learning, behavior, and result. The sampling technique used purposive research with research subjects consisting of trainees who had gotten a job and who had not gotten a job after attending training at BPTT, training implementers, instructors, and service users. Data were collected using questionnaires and in-depth interviews, and documentation. The results of the research show: (1) good response by the trainees on the reaction aspect; (2) changes or improvements in the knowledge and skills of the trainees have not been well measured in the learning aspect; (3) good response by service users on behavioral aspects; and (4) it is difficult for the training organizers to detect the number of training participants who have been absorbed or have not been absorbed into the workforce due to the lack of communication with participants who have attended training on the outcome aspect.